1989
DOI: 10.1111/j.1365-2621.1989.tb05148.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Collagen in Myocommata and Endomysium Fractions of Carp and Spotted Mackerel Muscle

Abstract: Preparation of myocommata and endomysium fractions Myocommata and endomysium fractions were prepared from the different parts of body muscle of carp and spotted mackerel. Both type I and V collagens were detected in the myocommata and endomysium fractions of both fish. The relative concentration of type V collagen to type I collagen was higher in the endomysium fraction than in the myocommata fraction. Both type I and V collagens were less soluble in the endomysium fraction than in the myocommata fraction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…This is a colorimetric method based on the oxidation of hydroxyproline with chloramine-T, followed by the addition of 4-dimethylaminobenzaldehyde, producing a coloured complex that was measured spectro-photometrically at 560 nm. To convert the quantity of hydroxyproline into collagen, a factor of 11.42 was used (Sato et al 1989) and expressed as mg/g fresh weight.…”
Section: Determination Of Total Collagenmentioning
confidence: 99%
“…This is a colorimetric method based on the oxidation of hydroxyproline with chloramine-T, followed by the addition of 4-dimethylaminobenzaldehyde, producing a coloured complex that was measured spectro-photometrically at 560 nm. To convert the quantity of hydroxyproline into collagen, a factor of 11.42 was used (Sato et al 1989) and expressed as mg/g fresh weight.…”
Section: Determination Of Total Collagenmentioning
confidence: 99%
“…1988). An aliquot of ASC was digested with pepsin to detect the presence of type V collagen by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE), as described previously (Sato et al. 1989b).…”
Section: Methodsmentioning
confidence: 99%
“…The amounts of the types I and V collagens in the ASC, PSC and ISC preparations were calculated on the basis of the hydroxyproline content of the hydrolyzates and the relative staining intensity of type V collagen α1(V) band as compared with the total collagenous bands on SDS‐PAGE gels, as described previously (Sato et al. 1989b).…”
Section: Methodsmentioning
confidence: 99%
“…2). Sato, Yoshinaka, Sato, and Tomita (1989) reported that the major collagen from the crustacean muscle was similar to type V collagen from the vertebrate muscle. The solubility of rainbow trout type V collagen increased during storage in ice, while no change in type I was observed, which may suggest that type V collagen is involved in the rapid softening of fish muscle (Sato, Ohashi, Ohtsuki, & Kawabata, 1991).…”
Section: Changes In Collagenmentioning
confidence: 98%